A Critical Review: Language Learning Strategy and Teachers’ Characteristics in Indonesian English Language Teaching - Oktaviyani, Emilda (Universitas Muhammadiyah Jember, 2017)
This paper discusses the relation between language learning strategy (LLS) and teachers’ characteristics. The objective of this study is to investigate the effect of teachers’ characteristics in students’ language learning strategy that will lead to the success of students in mastering English. The study was conducted by giving the teachers’ characteristics and LLS queationnaires to 50 secondary level students. This study employed descriptive qualitative method. The finding showed a positive correlation between teachers’ characteristics and students’ language learning strategy. Teachers’ characteristics strongly affect the way students learn. Once the students feel comfortable to the class and the teachers, it is just a piece of cake to master the lesson. In sum, as English teachers, it is better to mind our characteristics. Keywords: Teachers’ Characteristics, Students’ Language Learning Strategy (LLS) and EFL